Clinico-radiological features of brain metastases from thyroid cancer. Issue 48 (3rd December 2021) - Kim, Song Soo; Kim, Seok-Mo; Park, Mina; Suh, Sang Hyun; Ahn, Sung Jun
Abstract : Abstract: The brain is an unusual site for distant metastases of thyroid cancer. The radiological features of brain metastases (BMs) have rarely been reported. Hemorrhage is frequently noted in BMs from thyroid cancer. This study aimed to investigate the clinico-radiological features of BMs from thyroid cancer and to determine the risk factors to predict BM hemorrhage. We retrospectively evaluated the MR images of 35 patients with BMs from thyroid cancer at our hospital from 2013 to 2020. The number, size, site, presence of extra-cranial metastasis, presence of perilesional edema, intra-tumoral hemorrhage, enhancement pattern, and presence of diffusion restriction on MRI were described. We further classified the thyroid cancers into hemorrhagic and nonhemorrhagic groups to investigate the factors associated with hemorrhage. 54.29% of patients with thyroid BMs (19/35) had neurologic symptoms. 94.29% of patients (33/35) had extra-cranial metastases. The most common histology of primary thyroid cancer was papillary thyroid cancer (71.43%, 25/35), followed by anaplastic thyroid cancer (22.86%, 8/35). Thyroid cancer BMs were located mostly in the supra-tentorium (51.43%, 18/35) or both the supra and infra-tentorium (45.71%, 16/35). 60% of patients (21/35) showed hemorrhage within the BMs. The strongest predictor for BM hemorrhage was tumor size (variable importance: 50). Thyroid cancer BMs exhibit a bleeding tendency. Furthermore, larger BMs are more likely to have an intra-tumoral hemorrhage.